Pex1 loss-of-function in zebrafish is viable and recapitulates hallmarks of Zellweger spectrum disorders - Heins-Marroquin, Ursula; Hodzic, Zlatan; da Silva, Beatriz Soares Carneiro; Hendriks, Agnes; Gavotto, Floriane; Warmoes, Marc O.; Schlicker, Lisa; Omri, Samy; Jäger, Christian; Glaab, Enrico; Braverman, Nancy E.; Cordero-Maldonado, Maria Lorena; et al. (Frontiers in Molecular Neuroscience, 2025)
Zellweger spectrum disorders (ZSDs) are rare autosomal recessive conditions belonging to the larger group of peroxisome biogenesis disorders. The most prevalent form of ZSD is caused by mutations in the PEX1 gene, which encodes an AAA ATPase protein. Cells lacking functional PEX1 fail to import proteins crucial for the formation of competent peroxisomes, resulting in aberrant structures called ghost peroxisomes. Peroxisome dysfunction leads to the accumulation of compounds that are normally metabolized in this compartment, including very long-chain fatty acids (VLCFAs), pristanic and phytanic acids, as well as deficiency in compounds that are normally formed in this organelle, including docosahexaenoic acid (DHA) and plasmalogen precursors. Patients with a complete lack of PEX1 function develop severe symptoms and have a poor prognosis, with death in the first year of life. In the absence of effective treatments for ZSD, advancing our understanding of this complex multisystem disorder remains essential for uncovering new therapeutic opportunities. To this end, we generated and characterized a zebrafish model with Pex1 loss-of-function. Surprisingly, despite the early onset of disease-relevant features, about 10% of pex1–/– zebrafish reached adulthood. However, this resilience was short-lived, as none of the mutant fish survived beyond one year. Histopathological analysis of the liver in adult pex1–/– mutants revealed a profound peroxisomal import deficiency and severe vacuolation. Moreover, key metabolic hallmarks of ZSDs, including accumulation of VLCFAs and methyl-branched fatty acids phytanic and pristanic acid, were consistently detected in larval and adult pex1–/– mutants. Transcriptomics analysis in pex1–/– larvae revealed upregulation of ER-stress responses and pexophagy, as well as dysregulation of neurophysiological processes and visual perception. The latter findings were corroborated by abnormal locomotor behavior in the larvae and by disrupted outer nuclear and retinal layer architecture in adult mutant animals. The described zebrafish pex1 model provides a versatile in vivo platform to uncover novel disease-relevant pathways in ZSD and to investigate the physiological impact of VLCFAs and methyl-branched fatty acids. Its relative tolerance to Pex1 loss-of-function circumvents the early lethality observed in mouse models, enabling the study of ZSD pathophysiology beyond early developmental stages and offering a valuable tool for preclinical therapeutic exploration.